Edukasi Rhinitis: Mengenal, Mencegah, dan Mengatasinya Bersama untuk Meningkatkan Kualitas Hidup Masyarakat di Dayah Seumideun Kabupaten Pidie, Aceh - Tuti Sahara; Yusnidar Yusnidar; Iklima Iklima (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Rhinitis is one of the health conditions commonly found in the community, with a high prevalence both globally and in Indonesia. These disorders have a significant impact on an individual's quality of life, interfere with daily activities, and have the potential to lead to complications such as sinusitis and asthma. Educational efforts through health counseling are an important strategy in improving public knowledge, attitudes, and behaviors related to the prevention and management of rhinitis. This counseling activity aims to expand public understanding of rhinitis, including definitions, risk factors, symptoms, preventive measures, and self-management that can be applied in daily life. The methods used include interactive lectures, group discussions, and question and answer sessions, with the target of the general public who have risks or complaints related to rhinitis. The results of the activity showed a significant increase in participants' understanding of the condition of rhinitis and the importance of preventive measures. Participants showed a higher awareness of the importance of maintaining environmental cleanliness, avoiding exposure to allergens, and implementing a healthy lifestyle. In addition, there was an increase in participants' proactivity in seeking health information and a commitment to implement preventive behaviors consistently. This counseling has a positive impact on improving public health literacy and encouraging constructive changes in attitudes in dealing with rhinitis. It is hoped that similar activities can be carried out in a sustainable and widespread manner, so as to contribute to reducing the prevalence of rhinitis and improving the quality of life of the community in general. Community-based counseling has proven to be effective as a promotive and preventive approach in handling chronic and recurrent diseases such as rhinitis.